The Role Of New Media In The Teaching Of Communication Under The Integratin Of Media - et. al., Yuwei Li, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Although the application of new media in the teaching of communication is widespread, with the upgrading of teaching goals and content, this has always been a difficult subject to remain. The development background of media convergence also puts forward more dimensional requirements for news communication talents, to meet the professional requirements of the industry, improve teachers' communication teaching ability, and cultivate talents who master the theory of communication science and apply them proficiently. This paper takes the application of new media in the teaching practice of communication as a perspective, using literature analysis, investigation, and interview methods, analyze the advantages of new media in the teaching of communication, such as enrich teaching media, high efficiency, and environmental protection, and promotion of scientific evaluation, pay attention to the inefficiency of the utilization rate of new media teaching resources and the challenge of facing the design and management of online content, And to reduce the disadvantages, we can propose feasible countermeasures such as increasing the utilization rate of new media resources and strengthening teachers' media literacy.